APPROACHES FOR IMPROVING COMMUNICATION SKILLS OF RURAL ENGINEERING STUDENTS - Dr. Ananda Rao Bonthu; Venkata Ramana Manipatruni (Galaxy International Interdisciplinary Research Journal, 2022)
India is one of the developing countries having a lot of rural students but they are not properly utilized. Many of the students from urban areas having enough qualifications are getting good job opportunities. But the category which is the rural students is just having the dream of getting an employment. Employers prefer to hire and promote those persons who are resourceful, ethical and self-directed with good communication skills. Hard skills and experience are not at all enough for the competitive and escalation in the global world. The rural students also should get employment otherwise it will become very serious and critical. Rural students who are studying Engineering Education should be given opportunities to learn and practice interpersonal communication skills during their educational curriculum. In this paper the role of communication skill for the rural student in order to get better employment has been discussed. The communication skill Faculty has the responsibility of setting the stage for the Engineering students to get good communication skills when they are studying in the college itself. Once theory lectures are completed, faculty can develop strategies for improving communication skills. Students should participate in counseling, interviewing, and educational sessions. Also, students should participate in collaborative work with others. To ensure the development of communication skills in Engineering students, all the faculty who are teaching technical papers also incorporate the communication skill process into their teaching activities. By following these strategies, an institute can effectively and positively impact the communication skills of their rural students thereby they can get good job opportunities in the global world.